2019
DOI: 10.3390/rs11101257
|View full text |Cite
|
Sign up to set email alerts
|

Object-Based Time-Constrained Dynamic Time Warping Classification of Crops Using Sentinel-2

Abstract: The increasing volume of remote sensing data with improved spatial and temporal resolutions generates unique opportunities for monitoring and mapping of crops. We compared multiple single-band and multi-band object-based time-constrained Dynamic Time Warping (DTW) classifications for crop mapping based on Sentinel-2 time series of vegetation indices. We tested it on two complex and intensively managed agricultural areas in California and Texas. DTW is a time-flexible method for comparing two temporal patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 86 publications
1
62
0
1
Order By: Relevance
“…Among the multitude of potential curves, here we show two example cases: (i) with a small negative CC and (ii) with a strong positive CC. For each of the simulated pairs of time series, we estimate five CCs: (i) using the proposed methodology, (ii) using a slotting method with three different bin size (three, seven and 14 days), (iii) DTW with a Sakoe-Chiba band of 45 days (following [8]) and, when possible, using the simultaneous observations only. Figure 3 shows the observed distributions of these estimators.…”
Section: Validation Using Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the multitude of potential curves, here we show two example cases: (i) with a small negative CC and (ii) with a strong positive CC. For each of the simulated pairs of time series, we estimate five CCs: (i) using the proposed methodology, (ii) using a slotting method with three different bin size (three, seven and 14 days), (iii) DTW with a Sakoe-Chiba band of 45 days (following [8]) and, when possible, using the simultaneous observations only. Figure 3 shows the observed distributions of these estimators.…”
Section: Validation Using Simulationsmentioning
confidence: 99%
“…It consists in warping the time axis for an optimal alignment of the time series. It is possible to constrain the warping to consider only pairs of observations that are not too far from each other, e.g., the Sakoe-Chiba band [8]. The resulting time series share the same length but consist of padded sequences of the same values (when the time series are stretched) so the actual number of genuine observations is smaller.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic Time Warping (DTW) is an efficient solution for a non-linear alignment of two temporal sequences (Sakoe, Chiba, 1978). DTW obtained good crops classification results with a reduced number of training samples and with multi-temporal images that present gaps caused by the presence of clouds (Belgiu, Csillik, 2018;Csillik et al, 2019;Guan et al, 2018;Maus et al, 2016;Petitjean, et al, 2011). DTW has initially been developed for speech recognition applications (Sakoe, Chiba, 1978), and it has been adopted in other domains including medicine (Tsevas, Iakovidis, 2010) or robotics (Johnen, Kuhlenkoetter, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While in the pixel-based approach the reference for classification is the individual value of each pixel, without taking into account the neighborhood influence in the decision process, GEOBIA is characterized by the increase of information related to objects, such as shape, texture, compacity and context, which is useful to analyze heterogeneous landscapes (BLASCHKE, 2010). Recent studies have reported the advantages of detecting landscape changes via GEOBIA because it considers key factors that transcend reflectance values (SCHULTZ et al, 2016;CSILLIK, 2018;CSILLIK et al, 2019), outperforming pixel-based classification methods. In this context, considering that the generation of geo-objects may favor the detection of clearings in new frontiers of deforestation, such as Rondon do Pará, we adopted the objectoriented GEOBIA approach to perform land use and land cover (LULC) classifications in the present study.…”
Section: Introductionmentioning
confidence: 99%